Perbandingan Latihan Rondo Games dan Latihan Passing Diamond Terhadap Ketepatan Akurasi Passing Dalam Permainan Sepakbola - Faiz Ahmad Fahrevi; Muh Isna Nurdin Wibisana; Husnul Hadi (Journal of Physical Activity and Sports (JPAS), 2022)
This research is an experimental design with One-Group Pretest-posttest Design. The data analysis technique in this study uses t-test statistics. The test instrument uses a short pass developed by Bobby Charlton (2012: 3). The population in this study were all SSB players at the Parakan Temanggung Center. The sampling technique was total sampling. The mean result of the initial test from group 1, namely the rondo games practice, was 155.5 and the final test was 316.6. Meanwhile, the mean result of the initial test from group 2, namely the diamond passing practice was 155.5 and the final test was 233.3, the t-count value of the pretest and posttest of the experimental group I was -11.60 with sig = 0.000 and the t-table value was 2.120 and the t-count pretest and the posttest of the experimental group II was -8.854 with sig = 0.000 there was a difference in the accuracy of the passing accuracy of SSB players at the Parakan Center for Temanggung Regency between before and after being given rondo games and diamond passing exercises.Based on the rondo games exercise, the improvement was more significant than the diamond passing exercise on the accuracy of the passing of the SSB players at the Parakan Center for Temanggung Regency. Suggestions for players to further improve passing accuracy and for coaches are expected to provide rondo games and diamond passing exercises. Keywords: rondo games practice, diamond passing practice, soccer Abstrak Penelitian ini adalah eksperimen dengan desain One-Group Pretest-posttest Design.Teknik analisis data dalam penelitian ini menggunakan statistik uji-t. Instrumen tes menggunakan short pass yang dikembangkan oleh Bobby Charlton (2012 :3). Populasi dalam penelitian ini seluruh pemain SSB Puslat Parakan Temanggung.Teknik pengambilan sampel adalah total sampling. Hasil mean tes awal  dari kelompok 1 yaitu latihan rondo games adalah 155,5 dan tes akhir 316,6. Sedangkan untuk hasil mean tes awal  dari kelompok 2 yaitu latihan passing diamond adalah 155,5 dan tes akhir 233,3 nilai thitung pretest dan posttest kelompok eksperimen I adalah sebesar -11,60 dengan sig = 0,000 dan nilai ttabel adalah 2,120 dan nilai thitung pretest dan posttest kelompok eksperimen II adalah sebesar -8,854 dengan sig = 0,000 terdapat perbedaaan peningkatan ketepatan akurasi passing pemain SSB Puslat Parakan Kabupaten Temanggung antara sebelum dan setelah diberikan latihan rondo games dan latihan passing diamond. Berdasarkan Latihan rondo games lebih siginifikan peningkatannya daripada latihan passing diamond terhadap kemampuan akurasi ketepatan passing pemain SSB Puslat Parakan Kabupaten Temanggung. Saran bagi pemain untuk lebih meningkatkan lagi akurasi passing dan untuk pelatih diharapkan memberikan latihan rondo games dan latihan passing diamond. Kata kunci: Latihan rondo games, Latihan passing diamond, Sepakbola